Using the "gradient, two-point form", we have:
![(y - y1)/(x - x1) = (y2 - y1)/(x2 - x1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rpbhe0yuvmtvl98uxy8jnwykc22qt5wua6.png)
From the given data, we have that
![y2 = - 3 \\ y1 = 3 \\ x2 = 5 \\ x1 = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9yxxfr4qid7k8s2gjcdlpyge8qc8d857hl.png)
Therefore, substitute in the given values:
We have that:
![(y - (3))/(x - (0)) = (( - 3) - (3))/((5) - (0))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wdrnyh4srac3247n4kaaypfp8zxtfzhinn.png)
Simplify further
![(y - 3)/(x) = ( - 6)/(5)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1abgskkx29vyc7bpwu8beiijvif2skcy4y.png)
Multiply both sides by the LCM, 5x:
![5x( (y - 3)/( x) ) = 5x( ( - 6)/(5) )](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ma9g6mzzihagd1ee9h00rmo8faueyldjwd.png)
Simplify:
![5( y - 3) = x( - 6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lhe7zw5k8pemedjcndqk3tu22cb13dp4fu.png)
![5y - 15 = - 6x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/i26ouf8yeu8jazlfjex94yrm3v509nr63a.png)
Note that the equation of a straight line is given by Ax + By = C where A and B are coefficients of x and y respectively. C is the constant. Hence:
6x+5y=15